Low-temperature, high-stability, flexible thin-film transistors with a novel ScxIn1−xO3 semiconductor. (12th May 2016) - Song, Wei; Lan, Linfeng; Xiao, Peng; Lin, Zhenguo; Sun, Sheng; Li, Yuzhi; Song, Erlong; Gao, Peixiong; Zhang, Peng; Xu, Hua; Luo, Dongxiang; Xu, Miao; et al.
Abstract: Low-temperature scandium (Sc) incorporating In2 O3 (Sc x In1− x O3 ) thin films as oxide semiconductors were developed and investigated. And flexible thin-film transistors (TFTs) based on Sc x In1− x O3 channel layers were fabricated on polyethylene naphthalate substrate with the highest process temperature of only 150 °C. The Sc x In1− x O3 TFT displayed high on/off ratio of 10 7 with a turn-on voltage ( V on ) of only −0.1 V, a subthreshold swing of 0.21 V dec −1, and a mobility of 17.5 cm 2 V −1 s −1 . Furthermore, the flexible Sc x In1− x O3 TFTs exhibit high stability under both positive bias stability and negative bias stability, which was ascribed to little change of the lattice parameter of In2 O3 after incorporation with Sc (since the radius of Sc 3+ is similar to that of In 3+ ). More interestingly, the flexible Sc x In1− x O3 TFTs exhibited relatively good stability under negative bias illumination stability compared to those of IGZO TFTs, which was ascribed to fewer oxygen vacancies due to the strong bonding strength of Sc-O. Finally, the transfer curves of the Sc x In1− x O3 TFTs showed only a few changes under a curvature radius of larger than 20 mm.